Impact of hyperglycemia and antidiabetic medication on pancreatic uptake on [68Ga]Ga-DOTATOC PET/CT - Kunte, Sophie Carina; Siegmund, Thorsten; Tiling, Maximilian; Ostermair, Lukas; Unterrainer, Lena Maria; Theodoropoulou, Marily; Reincke, Martin; Völter, Friederike (Frontiers in Endocrinology, 2025)
IntroductionPositron-emission-tomography-(PET)/computed-tomography-(CT) using somatostatin-receptor-(SSTR)-binding radioligands is well established in the imaging of neuroendocrine tumors (NETs). SSTRs are expressed in NETs and endocrine and exocrine tissues, e.g. pancreas, where somatostatin binding to SST2 and SST5 inhibits glucagon and insulin secretion. Pancreatic background activity on SSTR-PET varies widely and is increased in up to 45% of cases. High uptake in the processus uncinatus can obscure NETs or cause false positives. The determinants of elevated pancreatic activity on SSTR-PET remain unclear, prompting investigation into the association between pancreatic radioligand uptake and diabetic status.MethodsAll patients with non-pancreatic NETs undergoing [68Ga]Ga-DOTATOC-PET/CT at LMU clinic with available HbA1c were included. Patients were grouped: without glucose metabolism disorder (HbA1c 4.0-5.6%), prediabetes (HbA1c 5.7-6.4%), type 2 diabetes mellitus. Pancreatic volume and tracer uptake were assessed, with correlation and regression analyses between SSTR expression and HbA1c.ResultsThe study included 40 patients (54 scans; n=22: normal glucose metabolism, n=20: prediabetes, n=12: diabetes; n=11: antidiabetic medication (AM)). Patients with normal glucose homeostasis showed increased tracer-uptake than those with impaired glucose metabolism (p=0.033; p=0.009). Correlation analysis revealed a significant negative correlation of HbA1c and SUVmax in patients without AM (r2 = 0.267; p<0.001). Multiple linear regression analysis with AM as a covariate revealed a significant association between HbA1c and SUVmax (r2 = 0.667; CI -0.371 to -0.135; p<0.001), AM was a significant covariate (CI 1.393 to 2.120; p<0.001). The association between HbA1c and SUVmean showed a trend (p=0.061) but no statistical significance.ConclusionOur findings indicate a significant association between pancreatic [68Ga]Ga-DOTATOC-uptake and glucose metabolism, suggesting that [68Ga]Ga-DOTATOC-PET/CT sensitivity for detecting pancreatic NETs may be affected by individual glucose homeostasis.